Inverse Trigonometric Functions – HSC Math

Posted In: Mathematics
  1. $sin^{-1}x+cos^{-1}x=π/2$
  2. $tan^{-1}x+cot^{-1}x=π/2$
  3. $sec^{-1}x+cosec^{-1}x=π/2$
  4. $sin^{-1}(-x)=-sin^{-1}x$
  5. $cos^{-1}(-x)=π-cos^{-1}x$
  6. $tan^{-1}(-x)=tan^{-1}x$
  7. $cot^{-1}(-x)=π-cot^{-1}x$
  8. $sec^{-1}(-x)=π-sec^{-1}x$
  9. $cosec^{-1}(-x)=-cosec^{-1}x$
  10. $sin^{-1}(1/x)=cosec^{-1}x$
  11. $cos^{-1}(1/x)=sec^{-1}x$
  12. $tan^{-1}(1/x)=cot^{-1}x$
  13. $sin^{-1}x+sin^{-1}y=sin^{-1}(x√{1-y^2}+y√{1-x^2})$
  14. $sin^{-1}x-sin^{-1}y=sin^{-1}(x√{1-y^2}-y√{1-x^2})$
  15. $cos^{-1}x+cos^{-1}y=cos^{-1}(xy-√{1-x^2}√{1-y^2})$
  16. $cos^{-1}x-cos^{-1}y=cos^{-1}(xy+√{1-x^2}√{1-y^2})$
  17. $tan^{-1}x+tan^{-1}y=tan^{-1}{x+y}/{1-xy}$
  18. $tan^{-1}x-tan^{-1}y=tan^{-1}{x-y}/{1+xy}$
  19. $2sin^{-1}(x)=sin^{-1}(2x√{1-x^2})$
  20. $2cos^{-1}(x)=cos^{-1}(2x^2-1)$
  21. $2tan^{-1}(x)=tan^{-1}{2x}/{1-x^2}=cos^{-1}{1-x^2}/{1+x^2}$
  22. $3sin^{-1}(x)=sin^{-1}(3x-4x^3)$
  23. $3cos^{-1}(x)=cos^{-1}(4x^3-3x)$
  24. $3tan^{-1}(x)=tan^{-1}{3x-x^3}/{1-3x^2}$
  25. $1/2sin^{-1}(x)=tan^{-1}{1-√{1-x^2}}/x$
  26. $1/2cos^{-1}(x)=cos^{-1}√{{1+x}/2}=sin^{-1}√{{1-x}/2}=tan^{-1}√{{1-x}/{1+x}}$
  27. $1/2tan^{-1}(x)=tan^{-1}{√{1+x^2}-1}/x$
  28. $sin^{-1}(x)=cos^{-1}√{1-x^2}$
    $=tan^{-1}x/√{1-x^2}$
    $=cot^{-1}√{1-x^2}/x$
    $=sec^{-1}1/√{1-x^2}$
    $=cosec^{-1}1/x$

Post Tags: HSC | Trigonometry


No Comments »


Leave a Reply

Your email address will not be published. Required fields are marked *